Sistem Pakar Menggunakan Forward Chaining dalam Mendeteksi Tingkat Keparahan Skizofrenia - Mirantie Prima Surya (Jurnal Informasi dan Teknologi, 2022)
The Basic Health Research Research (Riskesdas) in 2018 showed the prevalence of Schizophrenia in Indonesia was 7% per 1,000 households. The coverage of the indicator for Mentally Impaired Patients Getting Treatment and Not Abandoned (PGJMPTD) nationally is 38.14%, and West Sumatra Province for the same indicator with 45.58% is in the top fourth province with a score of 45.58%. This study aims to build an appropriate system for Schizophrenia indicators. The system built in the form of an Expert System. Expert systems are the ability of computers to convert knowledge from humans into computers and can help overcome problems that can only be solved by experts. An expert system for detecting the severity of Schizophrenia is a system that adopts the knowledge of a psychiatrist in determining the severity of Schizophrenia in a psychiatric patient. This expert system is made using the Forward Chaining method. The purpose of this Expert System is to prove that the Forward Chaining method can be implemented in making this Expert System. In addition, the Expert System can provide benefits to assist a Psychiatrist in conducting tests to determine the severity of Schizophrenia patients. The data used in this study were 20 medical records of patients, in the form of symptoms of the disease and data on patient diagnosis by a Psychiatrist Specialist. Furthermore, the data is processed using the Inference Forward Chaining method and presented in the form of an application using the PHP programming language. The results of this study are 18 valid data and 2 invalid data so that an accuracy value of 90% is obtained. The Expert System with the Forward Chaining method is suitable and can be used to detect the severity of Schizophrenia.